Direct and indirect costs of families with a child with acute lymphoblastic leukaemia in an academic hospital in China: a cross-sectional survey - Xin Li; Yijiong Ren (BMJ Open)
Objectives To estimate the direct and indirect costs in families with a child with acute lymphoblastic leukaemia (ALL) in China.Design A single-site, cross-sectional survey of primary caregiver of a child with ALL was performed.Setting and participants We analysed the total costs incurred on the completion of the first three-phase treatment (induction, consolidation and intensification), which requires intensive hospitalisation. Eligible patients were (1) diagnosed with ALL between 2010 and 2012 at Shanghai Children’s Medical Center (SCMC), (2) aged 0–14 years at diagnosis and (3) completed the first three-phase treatment at SCMC. The data were collected between October 2014 and December 2014.Outcome measures We decomposed the total costs into three categories: (1) direct medical costs, which were further divided into outpatient and inpatient costs; (2) direct non-medical costs, which referred to expenses incurred in relation to the illness; and (3) indirect costs due to productivity loss.Results A total of 161 patients were included in the study. Direct medical costs accounted for about 51.7% of the overall costs, and the rest of 48.3% of the total costs were attributed to direct non-medical costs and indirect costs. Regarding families with different household registration type (rural vs urban), the total costs were significantly different between the two groups (US$36 125 vs US$25 593; p=0.021). Specifically, urban families incurred significantly larger indirect costs than rural families (US$12 343 vs US$4157; p=0.018). Although the direct non-medical costs were not significantly different, urban families spent more money on hygiene cleaning products and auxiliary treatment equipment (p=0.041) and gifts and treats (p=0.034) than rural families.Conclusions The financial burden faced by the Chinese families with a child with ALL was tremendous, and the distributions of costs among the three categories were different between urban and rural families.